HUBUNGAN BIMBINGAN SOSIAL DENGAN INTERAKSI TEMAN SEBAYA PADA SISWA KELAS VIII SMPN 18 PONTIANAK - Muhlis, Muhlis; Asrori., H.M.; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe the relationship between social counseling with peer to interaction in students of class VIIIÂ state junior high school 18.Â The form of this study is the study of relationships. The population of this research are students of class VIII. Data collection techniques used are indirect communication techniques, in this study data collection tool used is the scale of psychology. Based on the results of data analysis shows that social guidance of class VIII in students reached 89% are in the category of